Penerapan Model Pembelajaran Problem Based Learning dengan Pemanfaatan Laboratorium sebagai Sumber Belajar untuk Meningkatkan Hasil Belajar Kimia Peserta Didik Kelas XII IPA 2 SMA Kristen 1 Metro - Nugraheni, Nugraheni (STKIP PGRI Bandar Lampung, 2023)
The aim research to implementation learning and result of kimia by method Problem Based Learning of students XII IPA 2 SMA Kristen 1 Metro. The method that research tes-non tes, observation, document, and interview. Research result of Kimia learn problem based learning. Pracycle, cycle I,cycle II,and cycle III to increase. Result pracycle flat 55,29%, cycle I 70%, cycle II 79,70%, and cycle III 78,64%. The finished learning pracycle 2,94, cycle I to 38,23%, cycle II 64,70%, and cycle III 100%.